Studi Korelasi Antara Prestasi Belajar Bidang Studi IPS dengan Kesadaran Nasional Pada Siswa Kelas III SMP Negeri 31 Halmahera Barat - Asnita Ode Samili; Jainudin Hasim; Yuni Andriyani Safitri; Fitriana Ibrahim (Jurnal Ilmiah Wahana Pendidikan, 2022)
The research with the title Study of correlation between learning achievement in the field of Civics and national awareness in third grade students of SMP country 31 West Halmahera. Which aims to find out several things, namely, the level of learning achievement in the field of Civics and the level of national awareness. The method used in obtaining this research data is the method of documentation and questionnaires. Analysis of data for learning achievement in the field of Civics and national awareness used the arithmetic mean formula. Meanwhile, to analyze the correlation between IPS learning achievement and the level of national awareness, the correlation technique is the crude product moment correlation. The results of the analysis of the existing data show that the average level of Civics learning achievement is sufficient with an average value of 72.66. Analysis of the high national awareness variable with an average value of 92.44. The correlation analysis between learning achievement in Civics Studies and national awareness shows a significant relationship. Learning achievement in the field of Civics, which is still in the good enough category, needs to be improved by improving the teaching and learning process, especially in providing motivation for students' learning so that students' national awareness needs to be improved or at least maintained.